IMPROVING FORENSIC MEDICAL EXAMINATION ACTIVITY IN SOLVING CRIMES: ON THE EXAMPLE OF THE FORENSIC BIOLOGY DEPARTMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The role of forensic medical examination bodies in the timely and complete detection of crimes is invaluable. Especially in crimes such as murder, infliction of bodily harm, theft, rape, and sexual assault, the identification of biological evidence is of great importance. Therefore, improving the efficiency of forensic medical experts and enhancing laboratory activities is one of the urgent tasks.